SHARI’A STATE AND THE MAKING OF CHRISTIAN’S POLYPHONIC NARRATIONS IN CONTEMPORARY ACEH, INDONESIA - Yaser Amri; Muhammad Ansor (UIN Sumatera Utara, 2021)
Abstract: There is an increasing interest in the study of Christian identity as a minority in a Muslim majority country. However, the study of plurality regarding the Christian identity considering the context of Islamic Sharia in Aceh is still limited. This article discusses the formation and representation of Christian identity in Aceh by focusing on how they negotiate internal aspirations in the context of Islamic Sharia. The data are based on in-depth interviews with fifteen Christian figures consisting of priests and religious leaders in five districts/cities in Aceh. The article argues that the internal and external dynamics of Christians influenced the narration of their identity in Aceh. The article shows the context of Islamic Sharia and the plurality of Christian internal aspirations resulting in unsimplifiable to a single genre, but rather polyphonic and sometimes mutually contested.Keywords: Aceh Christian, identity reproduction, sharia law